PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Umi Nur Janah; Kurnia Rina Ariani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze and the effect of investment decisions, funding decisions and dividend policies on firm value in financial sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The population in this study are financial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period, and obtained 33 companies as a sample. The sampling technique in this study used the purposive sampling method, namely the technique of determining the sample with certain criteria. While this type of research is quantitative research, and the data analysis method used is multiple linear regression analysis. The results of this study indicate that investment decisions and funding decisions have no significant effect on firm value, while dividend policy significantly affects firm value.